Desain Hydrolic System With Twin Brush Kart Sebagai Sarana Penunjang Percepatan Project Ship Maintenence - Angga, Anauta Lungiding A.R.; Retno, Retno Syahriawati Dewi; Sessy, Arisessy Maharani Mulananda (JURNAL ENGGANO, 2024)
ABSTRACT One of the tools that can assist in the maintenance process of a ship before it enters a dry dock is an underwater ship hull cleaner. The existing tools currently used are not yet widely available across Indonesia. Therefore, this research aims to plan the development of an underwater ship hull cleaner named the Twin Brush Kart. The objective is to determine an efficient system and design. The methodology involves collecting data on the number of shipyards and ships in Indonesia, as well as existing underwater ship hull cleaners. From the available hull cleaner data, this research adopts a hydraulic system. The hydraulic system offers advantages such as flexibility, versatility, and efficiency. The resulting design is user-friendly, with dimensions of 70 cm length, 55 cm width, and 16.7 cm height, and includes a control interface for the user. Additionally, the planned system is straightforward for users to understand, allowing for quick learning of the Twin Brush Kart. Based on the planning results, the specifications include a diesel engine with 14.55 kW of power, a hydraulic pump with a flow rate of 40.1 lpm and a working pressure of 185 bar, and a rotary actuator with a displacement of 19.9 cc and a rotational speed of 1000 RPM. Keywords: Hull, underwater cleaner, hydraulic system